Religiosity And Social Support Impact On Social Workers' Stress Levels - Saputri, Cut Rahmi; Qomariyah, Nurul (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
The social work profession in Indonesia is often viewed as a job that can be done by anyone, without understanding that this job contains high psychological pressure and can lead to work stress. This study aims to determine the effect of religiosity and social support on the level of work stress in social workers in Indonesia. This study uses a quantitative approach with a sample of 100 social workers who have at least one year of work experience. The sample was selected using a purposive sampling technique. The instruments used include the Work Stress Scale by Parker and DeCotiis (1983) to measure work stress, a religiosity scale adapted from Amir (2021), and a social support scale developed by Laksmita et al. (2020). All instruments use a 5-point Likert scale and have been proven to have high reliability (α > 0.85). Data analysis was carried out using multiple linear regression to test the effect of religiosity and social support on work stress. The results of the analysis showed that religiosity had a significant effect on work stress (p = 0.044), and social support also had a significant effect on work stress (p = 0.000). These findings underscore the importance of internal and external factors in reducing work stress in social workers.